2023
DOI: 10.21608/ejvs.2023.197750.1454
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Untreated Olive Pulp on Hematological and Growth Performance in Broiler Treated with NDvaccine

Abstract: A N objective study is on the olive oil by-product industry that may be used without a feedlot as compromising the taste, dietary, digestibility value, health, and growth performance of broilers. This investigation was conducted in order to determine the results of using untreated olive pulp on the hematological parameters and performance of broiler chickens. 180 one-dayold Ross chick's broilers came from a nearby commercial hatchery. The chicks were divided randomly into 4 groups, each group including (45) bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
1
Order By: Relevance
“…This may be attributed to the presence of growth-promoting compounds in dates that enhance energy and protein utilization, as suggested by [64,65] resulting in a better synchrony between energy release and protein degradation, leading to increased microbial protein yield. In contrast, our research contradicts prior studies by [62,66,67,68], who found no significant variations in the live BW and BWG of rabbits fed diets containing olive by-products.…”
Section: Discussioncontrasting
confidence: 99%
“…This may be attributed to the presence of growth-promoting compounds in dates that enhance energy and protein utilization, as suggested by [64,65] resulting in a better synchrony between energy release and protein degradation, leading to increased microbial protein yield. In contrast, our research contradicts prior studies by [62,66,67,68], who found no significant variations in the live BW and BWG of rabbits fed diets containing olive by-products.…”
Section: Discussioncontrasting
confidence: 99%